Biolistic Transformation of citrullus vulgaris Schrad (watermelon) - Suratman, F.; Huyop, Fahrul Zaman; Wagiran, A.; Rahmat, Z.; Ghazali, H.; Parveez, G. K. A. (Asian Network for Scientific Information, 2010)
In this study, DNA-coated gold particles were used to transform cotyledon sections including axillary meristem of Citrullus vulgaris using the biolistic method for optimizing the transformation parameters and eventually regeneration of putative transgenic watermelon plants. Initially, five biolistic parameters namely helium pressure, macrocarrier to target tissue distance, explant ages, DNA concentrations and osmotic treatment were optimized using plasmid pRQ6 (carrying both gusA and hpt genes). The optimized biolistic parameters for cotyledon sections of Citrullus vulgaris explants were determined as follow: 1100 psi helium pressure, 6 cm target distance, 4-day-old explants, concentration of DNA at 1.2 µg/bombardment and osmotic treatment for 24 h on medium supplemented with 0.6 M mannitol prior to bombardment. Using the optimized parameters, transformation of watermelon cotyledons was carried out using pAHG11, pCAMBIA 1301, co-transformation (pAHG11+pCAMBIA 1301) and pCambar plasmids. Bombarded tissue’s were selected on either 5 mg L-1 hygromycin or 2 mg L-1 PPT. Finally, the transformants produced were subjected to GUS histochemical assay. Integration of the transgenes into transgenic watermelon genome was confirmed by PCR analysis.